Correction: The fabrication of hollow ZrO2 nanoreactors encapsulating Au–Fe2O3 dumbbell nanoparticles for CO oxidation. Issue 16 (7th April 2022) - Yang, Fan; Wu, Chunzheng; Yu, Hongbo; Wang, Shiwei; Li, Tong; Yan, Bo; Yin, Hongfeng
Abstract : Correction for 'The fabrication of hollow ZrO2 nanoreactors encapsulating Au–Fe2 O3 dumbbell nanoparticles for CO oxidation' by Fan Yang et al., Nanoscale, 2021, 13, 6856–6862, DOI: ; 10.1039/D1NR00173F